Strengthening the Role of Universities in the National Agricultural Research Systems in Sub-Saharan Africa. Highlights of a Workshop - Michelsen, Heike; Shapiro, D. (International Service for National Agricultural Research, 1998)
This brief report summarizes the outputs of the final workshop of the collaborative project ""Strengthening the role of universities in NARS"", which was held in Cotonou, Benin, November 17-21, 1997. The workshop synthesized the experiences and results of the six case studies carried out in the project in Benin, Burkina Faso, Côte-d'Ivoire, Nigeria, Uganda, and Zimbabwe. The overall purpose was to draw lessons and identify procedures for improving universities' research performance and links with other components of the national agricultural research systems. The report includes background information on the study, as well as summaries of the main workshop presentations and discussions.